Pharmacological treatment of hypertension guided by peripheral or central blood pressure: a comparison between the two strategies - Guimarães Filho, Gilberto Campos; de Oliveira Vitorino, Priscila Valverde; Inuzuka, Sayuri; Barroso, Adriana Sebba; Pacífico Alves Filho, Robson Pierre; Melo, Victoria Alves; de Oliveira Urzeda, Luiz Fernando; Lima Sousa, Ana Luiza; Coca, Antonio; Veiga Jardim, Paulo César Brandão; Barroso, Weimar Kunz Sebba (Frontiers in Cardiovascular Medicine, 2023)
Background Arterial hypertension treatment guided by central blood pressures (CPB) rather than peripheral blood pressures (PBP) measurement has the potential to show greater effectiveness in preventing or even regressing stiffness and target organ damage (TOD). Objective This study aimed to compare the parameters of CBP and PBP measurements, arterial stiffness, TOD and renal profile in patients with anti-hypertensive treatment guided by CBP or PBP targets. Methods A randomized clinical trial was conducted in central group (CG) and peripheral group (PG). Patients were randomized, evaluated every 3 months for BP and antihypertensive adjustments during a one-year follow up. The procedures in V1 and V5: anthropometric assessment; CBP/PBP measurements, carotid ultrasound; echocardiography; laboratory tests. Paired and unpaired t-tests and the χ2 were used (significance level: 5%). Results The study evaluated 59 participants (30CG/29PG). The augmentation index (AIx) was higher in the CG (27.3% vs. 20.3%, p = 0.041). Intergroup analysis has found central diastolic BP lower in the CG (78.9 vs. 84.3 mmHg, p = 0.024) and the Alx difference between groups ceased to exist after a one-year follow-up. Intragroup comparisons, after intervention, showed a lower frequency of changed PWV (p < 0.001) and LVMI (p = 0.018) in the CG. The PG showed a higher frequency of changed PWV (p < 0.001) and LVMI (p = 0.003). Conclusion The intervention guided by central BP reduced the central diastolic BP and AIx compared to the PG. There was a reduction in the frequency of changed PWV and LVMI in the CG.